Rank and Performance in Dynamic Tournaments: Evidence From the PGA Tour. (May 2019) - Hickman, Daniel C.; Kerr, Craig; Metz, Neil
Using data from the final round of golf tournaments, we analyze the effect of player rank on performance. The identification of varying levels of pressure is possible due to the detailed nature of the data set, which allows us to determine the rank of each player just prior to teeing off on each hole. We find that players in the lead tend to underperform, especially near the very end of the tournament and when the lead is closely contested. We also create a measure to rank individual golfers based on how their performance is affected by high-pressure situations.